2020
DOI: 10.1155/2020/5024830
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Analysis of a Stochastic Hybrid Logistic Model with Delay and Two-Pulse Perturbations

Abstract: In this paper, we propose and discuss a stochastic logistic model with delay, Markovian switching, Lévy jump, and two-pulse perturbations. First, sufficient criteria for extinction, nonpersistence in the mean, weak persistence, persistence in the mean, and stochastic permanence of the solution are gained. Then, we investigate the lower (upper) growth rate of the solutions. At last, we make use of Matlab to illustrate the main results and give an explanation of biological implications: the large stochastic dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In this study, the polarity is identified by injecting pulse voltage into the hypothesized 􏽢 d axis. IPMSM transforms voltage and current components in the stationary coordinate system in accordance with Euler's theorem to yield the resultant vector equation [18][19][20][21][22][23][24][25], which is expressed as…”
Section: Polarity Identification By Pulse Voltage Injection Methodmentioning
confidence: 99%
“…In this study, the polarity is identified by injecting pulse voltage into the hypothesized 􏽢 d axis. IPMSM transforms voltage and current components in the stationary coordinate system in accordance with Euler's theorem to yield the resultant vector equation [18][19][20][21][22][23][24][25], which is expressed as…”
Section: Polarity Identification By Pulse Voltage Injection Methodmentioning
confidence: 99%
“…For example, Li and Guo [15] presented a stochastic SIS epidemic model in which they mixed three types of noise, namely, white noise, colored noise, and Lévy noise. In the works [16,17], the authors proposed models with delay and Markovian switching for ecological populations. We can use the telegraph (or colored) noise to describe the mutation of the system from one state to another.…”
Section: Introductionmentioning
confidence: 99%